Estimation of soil loss by the USLE model in a mountain basin in the south of Santa Catarina state, Brazil - Amaral, Lucas Kister; Cadorin, Sabrina Baesso; Back, Álvaro José; Szymanski, Fernanda Dagostin; Corseuil, Claudia Weber (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Water erosion is a factor of soil degradation that is triggered by the impact of raindrops originated by intense rainfall disaggregating the soil, followed by the carrying of particles by surface runoff. In the erosion process, in addition to soil loss, nutrients, fertilizers, and pesticides are carried resulting in water courses and water pollution. Erosion can have a major impact on agricultural production, when soil use and management techniques are not used. Therefore, this study aimed to evaluate the soil loss in the Malacara river basin, which is a sub-basin of the Mampituba river basin characterized by a contrasting relief, with high altitudes in the escarps of Serra Geral and floodplain. The method used for the development of this research was the application of the Universal Soil Loss Equation (USLE). USLE soil loss estimation requires the following factors: rainfall erosivity (R), soil erodibility (K), slope length (L), slope steepness (S), soil use and management (C), and erosion control practice factor (P). The estimated rainfall erosivity was 5,754.2 MJ mm ha-1 h-1 year-1. Erodibility was determined for the soils present in the basin, highlighting a high value for gleysoil. The topographic factor (LS) showed values from 0 to greater than 20, which corresponds to the low to very high runoff potential. The floodplain showed lower runoff rates, while for the locations close to the enclosed valleys in the Malacara canyon, the runoff potential varied from high to very high. The soil use and management factors and conservation practices (CP) obtained a maximum value of 0.404, corresponding to the exposed soil; the second most representative class was agricultural areas, with a value of 0.145. The soil loss in the Malacara river basin varied from 0 to more than 200 t ha-1 year-1. In fact, 87.38% of the area presents a degree of sheet erosion normal to slight and, only 2.94% of the area has a high or very high degree of erosion. Moreover, due to the relief characteristics with shallow soils and intense rainfall in mountainous basins, knowing and understanding soil losses due to erosion is crucial for the adequate management of water resources in river basins.